Materiais híbridos de sílica/orgânico dopados com rodamina-B: estudo da luminescência e preparação de filmes finos para aplicações em fotônica - Manoel, Diego da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Organic-Inorganic Hybrids Materials (OIHM) prepared by sol-gel process show the principal properties and characteristics from both organic and inorganic constituents. These materials can to be obtained such as fine powders, vitreous gels and thin films, with applications in different areas, as protective coatings, optics and photonics. Silica/organic hybrid materials also known as ORMOSIL (Organically Modified Silicates) prepared by sol-gel process are extensively studied due the synergistic multifunctional properties from the silica and the organic polymers. During the sol-gel synthesis these Silica/organic colloidal hybrids can be doped with photoactive organic chromophores with different optical properties, allowing preparation of advanced photoactive materials. In the large range of photoactive organic materials one of interest is the Rhodamine-B, a laser dye which presents tunable emission and high quantum yield. In this work we studied the Rhodamine-B fluorescence and wavelength of emission in function of the concentration of Rhodamine-B doped into the silica/organic hybrid sol derived from glycidoxypropyltrimethoxysilano (GPTS) and tetraethylorthosilicate (TEOS). The changes in the intensity and wavelength emissions of silica/organic hybrid sol samples with different concentrations Rhodamine-B were quantified and was possible to determine the concentration of Rhodamine-B which yields the highest emission intensity in the sol samples. The sample with the highest emission intensity was used to synthesize thin films onto glass slides by dip-coating technique and these films were characterized by UV-VIS optical absorption and fluorescence measurements. The obtained Rhodamine-B-doped silica/organic films showed excellent optical quality, and were used for femtosecond laser microfabrication of waveguides onto the films surface

Através do processo sol-gel é possível produzir materiais Híbridos Orgânicos/Inorgânicos (OIHM - Organic-Inorganics Hybrid Materials), os quais unem as principais propriedades de seus constituintes. Estes materiais podem ser obtidos em diversas formas como partículas, fibras, géis vítreos e filmes finos, com aplicações em diversas áreas, como proteção de superfícies, na óptica e na fotônica. Os híbridos de Sílica/orgânico preparados via processo sol-gel são conhecidos como ORMOSIL (Organically Modified Silicates) e são amplamente estudados devido à união das propriedades da sílica e dos polímeros orgânicos. É possível incorporar nos híbridos de Sílica/orgânico ainda na fase líquida (sol) diversos materiais orgânicos com diferentes propriedades ópticas, possibilitando a obtenção de materiais fotoativos avançados. Dentre os materiais orgânicos opticamente ativos destacamos os corantes lasers, dentre eles a Rodamina-B, que possuí propriedades de grande interesse, como comprimento de onda de emissão bem definido e alta eficiência quântica. Neste trabalho estudamos e modelamos matematicamente a luminescência e o comprimento de onda de emissão da Rodamina-B em função de sua concentração nos híbridos de sílica/orgânico ainda na fase sol, preparados à base dos alcóxidos glicidoxipropiltrimetoxisilano (GPTS) e tetraetilortosilicato (TEOS). Desta maneira quantificamos a variação tanto na intensidade como no comprimento de onda de luminescência do sol de sílica/orgânico dopado com Rodamina-B, e foi possível definir a concentração de Rodamina-B para maximização da intensidade de emissão das amostras. O sol de sílica/orgânico dopado com Rodamina-B que apresentou máxima intensidade de luminescência foi utilizado para a síntese de filmes finos pela técnica de dip-coating, e obtivemos filmes finos com excelente qualidade óptica. Os filmes foram caracterizados por medidas de absorção...
Keywords: Física aplicada; Processo sol-gel; Filmes finos; Silica; Luminescencia